2019
DOI: 10.3390/ma12193088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preheating on the Microstructure Evolution of Laser Re-Melting Thermal Barrier Coatings/Ni-Based Single Crystal Superalloy Multilayer System

Abstract: Laser surface re-melting (LSR) is a well-known method to improve the properties of atmospheric plasma-spraying thermal barrier coatings (APS TBCs) by eliminating the voids, incompletely melted particles and layered-structure. Laser energy density should be carefully selected to reduce the exposed thermal damage of the underlying single crystal (SX) matrix. Therefore, the purpose of this paper was to identify the effect of introducing induction heating to laser modifying of APS TBCs coated on Ni-based SX supera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Specifically, the water-blown TBCs exhibited no recrystallization structure after the heat experiment. The combined method of adopting low laser energy and preheating at elevated temperatures can significantly lower the heat input into the single crystal (SX) matrix and, correspondingly, the interface stored energy, which can effectively lower the tendency for surface recrystallization after subsequent heat treatment [ 23 ]. At present, research on surface recrystallization of single crystal superalloys is mainly focused on the microstructure transformation of recrystallization zones [ 24 , 25 ], the factors leading to recrystallization itself [ 26 , 27 ] and the influence of recrystallization on the mechanical properties of the alloys [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the water-blown TBCs exhibited no recrystallization structure after the heat experiment. The combined method of adopting low laser energy and preheating at elevated temperatures can significantly lower the heat input into the single crystal (SX) matrix and, correspondingly, the interface stored energy, which can effectively lower the tendency for surface recrystallization after subsequent heat treatment [ 23 ]. At present, research on surface recrystallization of single crystal superalloys is mainly focused on the microstructure transformation of recrystallization zones [ 24 , 25 ], the factors leading to recrystallization itself [ 26 , 27 ] and the influence of recrystallization on the mechanical properties of the alloys [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The γ′ phase is the precipitation strengthened phase with a stoichiometric ration of Ni 3 Al. Al, Ti, Ta, Nb, and so on can be dissolved, which are named as γ′ phase elements [ 8 , 9 , 10 , 11 , 12 ]. With the rapid consumption of a large number of alloying element on the high-temperature environment, the original stable γ/γ′ structure will be destroyed [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid consumption of a large number of alloying element on the high-temperature environment, the original stable γ/γ′ structure will be destroyed [ 10 , 11 ]. Therefore, the long-term service performance of the superalloy in harsh temperatures is often related to its composition components and constitute elements [ 12 ]. Thus, in the current superalloy design, the composition of the alloy is often considered and studied to have better high-temperature oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al researched the ablation of metals coated with ceramic TBCs using nanosecond pulse fiber lasers, and found that the recast layer, edge protrusions and microcracks could not be eliminated due to the thermal effects during nanosecond laser drilling [ 16 ]. Fan et al used Nd: YAG (JK300D Nd: YAG pulsed laser, GSI, Birmingham, UK) pulsed laser to process Ni-based superalloy with TBCs, and found the maximum crack length reaches up to approximate 320 μm and the maximum crack width is approximate 50 μm [ 17 ]. In picosecond and femtosecond ultrashort pulse laser machining, these problems can be significantly improved, but for hole drilling [ 18 , 19 , 20 ], there is still a recast layer which thickness is about 5 µm after femtosecond ultrashort pulse trepanning [ 20 ].…”
Section: Introductionmentioning
confidence: 99%